Antimicrobial activity of tiger's betel (Piper porphyrophyllum NE Br., Piperaceae) - Wiart, C.; Hannah, N.A.; Yassim, M.; Hamimah, H.; Sulaiman, M. (2004)
The ethanol extract of leaves of Piper porphyrophyllum N.E. Br. showed a broad spectrum of antibacterial activity. The activity was increased on fractionation (hexane, dichloromethane and aqueous), particularly in the aqueous fraction. No activity was shown against tested Candida albicans.